The role of trust as a mediator on the effect of productivity in the fishing-industry supply chain performance in Riau, Indonesia - Yulinda, Eni; Kamisah, Supian; Saad, Mazni (2021)
This survey research was conducted from August to October 2020 in Rokan Hilir, one of the largest fishing industry centers in Riau Province, Indonesia. There are two research objectives, namely to analyze the influence of productivity on the fishing industry supply chain performance, and the role of trust as a mediator in the influence of productivity on the fishing industry supply chain performance in Rokan Hilir. 270 fishing companies were respondents, using the Slovin formula. The hypothesis was tested by the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results show that all dimensions can reflect their respective latent variables (productivity, trust, and performance), so that they can be used as model estimators. Furthermore, the results of hypothesis testing show that productivity, both directly and through trust mediation, has a significant effect on the fisheries industry supply chain performance.